Dynein light chain 8a of Toxoplasma gondii, a unique conoid‐localized β‐strand‐swapped homodimer, is required for an efficient parasite growth. Issue 3 (11th December 2012) - Qureshi, Bilal M.; Hofmann, Natalie E.; Arroyo‐Olarte, Ruben D.; Nickl, Bernadette; Hoehne, Wolfgang; Jungblut, Peter R.; Lucius, Richard; Scheerer, Patrick; Gupta, Nishith
Abstract : Dynein light chain 8 (DLC8) is a ubiquitous eukaryotic protein regulating diverse cellular functions. We show that the obligate intracellular parasite Toxoplasma gondii harbors 4 DLC8 proteins ( Tg DLC8a–d), of which only Tg DLC8a clusters in the mainstream LC8 class. Tg DLC8b–d proteins form a divergent and alveolate‐specific clade. Tg DLC8b–d proteins are largely cytosolic, whereas Tg DLC8a resides in the conoid at the apical end of T. gondii The apical location of Tg DLC8a is also not shared by its nearly identical Eimeria ( Et DLC8a), Plasmodium ( Pf DLC8), or human ( Hs DLC8) orthologs. Notwithstanding an exclusive conoid targeting, Tg DLC8a exhibits a classical LC8 structure. It forms a homodimer by swapping of the β2 strands that interact with the antiparallel β1 ′ strands of the opposing monomers. The Tg DLC8a dimer contains two identical binding grooves and appears to be adapted for multitarget recognition. By contrast, the previously reported Pf DLC8 homodimer is shaped by binding of the β0 strand with the parallel β2 ′ strand and lacks such a distinct binding interface. Our comparisons suggest an unexpected structural and functional divergence of the two otherwise conserved proteins from apicomplexan parasites. Finally, we demonstrate that a phosphomimetic S88E mutation renders the Tg DLC8a‐S88E mutant monomeric and cytosolic in T. gondii, and its overexpression inhibits the parasite growth in human fibroblasts.—Qureshi, B. M., Hofmann, N. E., Arroyo‐Olarte, R. D., Nickl, B., Hoehne, W., Jungblut, P. R., Lucius, R., Scheerer, P., Gupta, N. Dynein light chain 8a of Toxoplasma gondii, a unique conoid‐localized β‐strand‐swapped homodimer, is required for an efficient parasite growth. FASEB J. 27, 1034–1047 (2013). www.fasebj.org